5.4k views
0 votes
Help me on this math shiiii

Help me on this math shiiii-example-1
User Porg
by
5.0k points

1 Answer

4 votes

When you multiply two powers of the same base, you sum the exponents:


a^b\cdot a^c = a^(b+c)

So, in this case,


4^4\cdot 4^(-9) = 4^(4-9) = 4^(-5)

Now, negative exponents works like positive exponents, except you have to invert the number: i.e.


a^(-b) = (1)/(a^b)

So, you have


4^(-5) = (1)/(4^5)

User Spassas
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.